ASSOCIATION BETWEEN THE SUPERIOR ATTACHMENT OF THE UNCINATE PROCESS AND LOCALIZED FRONTAL SINUS OPACIFICATION ON COMPUTED TOMOGRAPHY THROUGH COMPARISON WITH THE ANTERIOR ETHMOID SINUS (Tạp chí Y học Cộng đồng, 2026)
Objectives: To determine the prevalence of superior uncinate process attachment variants according to the Landsberg C Friedman classification and to analyze the association between lamina papyracea attachment and localized frontal sinus opacification on computed tomography through comparison with anterior ethmoid sinus opacification, thereby evaluating the location-specific tendency of this association.Subjects and Methods: A cross-sectional analytic study was conducted on 211 sinus sides from 109 patients undergoing multidetector computed tomography at Nhan Dan Gia Dinh Hospital from January 2024 to June 2025. Superior attachment of the uncinate process (SAUP) was identified on coronal images. Frontal and anterior ethmoid sinus opacification was evaluated using the Lund-Mackay score (≥1). Cluster-robust confidence intervals were used to account for within-patient correlation.Results: The uncinate process attaching to the lamina papyracea (Type 1) was the most prevalent variant (52.1%), followed by skull base attachment (Type 2) at 16.6% and middle turbinate attachment (Type 3) at 12.3%. Frontal sinus opacification was present in 16.1% of sinus sides (34/211). The lamina papyracea attachment group had a higher prevalence of frontal sinus opacification than other attachment groups: 22.7% versus 8.9% (OR = 3.01; 95% cluster-robust CI 1.48–6.12; p = 0.002). For the anterior ethmoid sinus, no significant difference was observed between the two groups (43.6% vs. 37.6%; OR = 1.28; 95% CI 0.74–2.22; p = 0.372). Interaction analysis suggested a weaker association for anterior ethmoid opacification than for frontal sinus opacification (interaction OR = 0.43; 95% CI 0.18–1.01; p = 0.053).Conclusion: Attachment of the uncinate process to the lamina papyracea is the most common anatomical variant and is associated with frontal sinus opacification on computed tomography. The absence of a corresponding significant association with anterior ethmoid sinus opacification, together with a borderline interaction result, suggests a tendency toward a location-specific effect in the frontal recess and should be interpreted cautiously.
Keywords: Uncinate process, frontal recess, lamina papyracea, frontal sinus opacification, computed tomography.